Effectiveness of Surgical Decompression in Patients With Degenerative Cervical Myelopathy: Results of the Canadian Prospective Multicenter Study. Issue 5 (November 2021) - Karim, Mohammed S; Cadotte, David W; Wilson, Jefferson R; Kwon, Brian K; Jacobs, Bradley W; Johnson, Michael G; Paquet, Jérôme; Bailey, Christopher S; Christie, Sean D; Nataraj, Andrew; Attabib, Najmedden; Phan, Philippe; et al.
Abstract : BACKGROUND: : Conflicting evidence exists regarding the effectiveness of surgery for degenerative cervical myelopathy (DCM), particularly in mild DCM. OBJECTIVE: : To prospectively evaluate the impact of surgery on patient‐reported outcomes in patients with mild (modified Japanese Orthopaedic Association [mJOA] ≥ 15), moderate (mJOA 12‐14), and severe (mJOA < 12) DCM. METHODS: : Prospective, multicenter cohort study of patients with DCM who underwent surgery between 2015 and 2019 and completed 1‐yr follow‐up. Outcome measures (mJOA, Neck Disability Index [NDI], EuroQol‐5D [EQ‐5D], Short Form [SF‐12] Physical Component Score [PCS]/Mental Component Score [MCS], numeric rating scale [NRS] neck, and arm pain) were assessed at 3 and 12 mo postoperatively and compared to baseline, stratified by DCM severity. Changes in outcome measures that were statistically significant ( P < .05) and met their respective minimum clinically important differences (MCIDs) were deemed clinically meaningful. Responder analysis was performed to compare the proportion of patients between DCM severity groups who met the MCID for each outcome measure. RESULTS: : The cohort comprised 391 patients: 110 mild, 163 moderate, and 118 severe. At 12 mo after surgery, severe DCM patients experienced significant improvements in all outcome measures; moderate DCM patients improved in mJOA, NDI, EQ‐5D, and PCS; mild DCM patients improved in EQ‐5D and PCS. There was no significant difference between severity groups in the proportion of patients reaching MCID at 12 mo after surgery for any outcome measure, except NDI. CONCLUSION: : At 12 mo after surgery, patients with mild, moderate, and severe DCM all demonstrated improved outcomes. Severe DCM patients experienced the greatest breadth of improvement, but the proportion of patients in each severity group achieving clinically meaningful changes did not differ significantly across most outcome measures. Graphical Abstract : Figure. Graphical Abstract